AN APPROACH TO FINANCIAL STATEMENT ANALYSIS. - Allyn, Robert G. (The Accounting Review, 1944)
Abstract The public accountant and the company auditor, for instance, and possibly the firm's bookkeeper, have a twofold task at the end of the fiscal period, that of preparing financial statements and that of analyzing them by means of ratios and percentages. These results, arranged in proper form, are then submitted to the executive, who upon comparison with figures for former periods calculates trends of income, cost, tendencies toward overexpansion, overtrading, and many other problems of business management. To begin, the credit grantor analyzes the figures submitted to him for credit extension primarily to learn something of the debt-paying power of his firm's prospective customers. He is concerned less, if at all, with fixed asset valuation and the possibilities of a cash settlement through insolvency proceedings. Consequently, his scrutiny is centered upon that portion of the balance sheet which will reveal to him the working capital condition of his prospective customers. After the credit grantor has segregated the current portion of the balance sheet from the fixed, it is advisable that the credit investigator evaluate roughly the prospective customer's itemized current assets and liabilities to determine their worth.